Development of in vitro propagation system for Atriplex halimus L. - Aldahhak, O.; Zaid, S.; Abdul-Kader, A. M. (International Journal of Horticultural Science, 2014)
Explants excised from adult shrubs were surface sterilized and cultured on Murashige and Skoog (MS) basal medium in the presence of plant growth regulators (PGRs) at different concentrations. A high multiplication rate of 7.2-fold was achieved every four weeks on MS medium supplemented with 4.44 μM BA, 0.49 μM IBA and 0.58 μM GA3. Rooting was achieved with 73% efficiency within 2-4 weeks on agar-gelled MS basal medium free of PGRs. Rooted plantlets were gradually acclimatized to field conditions over 5-6 weeks with 65% efficiency. For in vitro selection for salt tolerance, MS medium was supplemented with increasing concentrations of NaCl ranging between 25 and 1000 mM. This study has demonstrated that in vitro shoots could tolerate up to 600 mM NaCl with optimal growth at 200 mM, while higher concentrations of NaCl affected growth negatively. Growth and shoot number decreased with increasing NaCl concentration with all plantlets died at 1000 mM NaCl.